The relationship of emotional intelligence to the dimensions of transformational leadership An applied study on the teachers of the Institute of Science and Technology for physical and sports activities - Boukhalfa, Hamza; Ben Shikh, Youcef (Journal of Educational and Psychological Sciences, 2019)
This study aims to study the relationship between emotional intelligence and the dimensions of transformational leadership among the teachers of the Institute of Science and Technology for physical and sports activities at the University of Mohammed Boudiaf in M’sila. It also aims to identify differences in the degree of emotional intelligence and leadership dimensions. The application of two measures of emotional intelligence and the other of the transformational leadership on a random sample of 30 teachers and the results indicate a relationship between the attributes of transformational leadership and emotional intelligence in the study sample. The results also revealed significant differences. The results of the study showed that the degree of the practice of transformational leadership was moderate. The research also identifies the most important recommendations: the need to review the criteria in which university leaders are chosen to be more in tune with the requirements of contemporary changes it supports transformational leadership in universities, attracting and retaining creators, and the need to design training seminars that value the role of emotional intelligence
Keywords: emotional intelligence; transformational leadership